(untitled) (Research, Society and Development, 2020)
The crop (Triticum aestivum) of wheat expresses great importance as food in the world. Knowing this, increasing the productivity of this crop is an excellent line of research, contributing to increase the supply of food. Thus, the objective of the work was to evaluate the development and productivity of the wheat crop with sequential applications of Azospirillum in the wheat crop. The experiment was carried out in the municipality of Guarapuava-PR, in the Center-South region of Paraná, with a humid mesothermal Cfb - subtropical climate, with an altitude of approximately 1120 m. To conduct the work, a randomized block design was used with five treatments, namely: Absolute control - T1 (without foliar application of Azospirillum brasilense), application of Azospirillum brasilense inoculant in tillering - T2, application of inoculant in tillering + elongation - T3, inoculant application in tillering + elongation + rubber - T4, inoculant application in tillering + elongation + rubber + flowering - T5, with 4 repetitions, totaling 20 sample units. After the application of leaf treatments, the evaluations of: (total mass of plant, mass of a thousand grains, productivity, hectoliter weight and plant height) were carried out. The application of Azospirillum brasilense foliar, regardless of the sum of application times, did not interfere with the development of the wheat crop, nor did it increase the productivity of the crop.